Hypermobile Ehlers-Danlos syndrome and spontaneous CSF leaks: the connective tissue conundrum - Severance, Sydney; Daylor, Victoria; Petrucci, Taylor; Gensemer, Cortney; Patel, Sunil; Norris, Russell A. (Frontiers in Neurology, 2024)
Collagen, the most abundant protein in the body, is a key component of the extracellular matrix (ECM), which plays a crucial role in the structure and support of connective tissues. Abnormalities in collagen associated with connective tissue disorders (CTD) can lead to neuroinflammation and weaken the integrity of the blood-brain barrier (BBB), a semi-permeable membrane that separates the brain's extracellular fluid from the bloodstream. This compromise in the BBB can result from disruptions in ECM components, leading to neuroinflammatory responses, neuronal damage, and increased risks of neurological disorders. These changes impact central nervous system homeostasis and may exacerbate neurological conditions linked to CTD, manifesting as cognitive impairment, sensory disturbances, headaches, sleep issues, and psychiatric symptoms. The Ehlers-Danlos syndromes (EDS) are a group of heritable CTDs that result from varying defects in collagen and the ECM. The most prevalent subtype, hypermobile EDS (hEDS), involves clinical manifestations that include joint hypermobility, skin hyperextensibility, autonomic dysfunction, mast cell activation, chronic pain, as well as neurological manifestations like chronic headaches and cerebrospinal fluid (CSF) leaks. Understanding the connections between collagen, CSF, inflammation, and the BBB could provide insights into neurological diseases associated with connective tissue abnormalities and guide future research.